2022
DOI: 10.3390/ma15031216
|View full text |Cite
|
Sign up to set email alerts
|

Review on Micro-Alloying and Preparation Method of 7xxx Series Aluminum Alloys: Progresses and Prospects

Abstract: Notably, 7xxx series aluminum alloy has become the most popular nonferrous alloy, extensively used in industry, construction and transportation trades, due to its high comprehensive properties such as high static strength, high strength, heat resistance, high toughness, damage resistance, low density, low quenching sensitivity and rich resource. The biggest challenge for aluminum alloy today is to greatly improve the corrosion resistance of the alloy, while maintaining its strength. The preparation method of 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…The simulation of the ECAP process, it was observed that the components experienced excessive skewing, necessitating an update to the mesh system. Remeshing criteria were established, with a 0.2 mm change in strain and a 1 mm element size selected as the criteria for remeshing [12]. In Figure 2, the ECAPed material was modeled using both strain hardenable rigid-plastic modes and isotropic linear elastic modes.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…The simulation of the ECAP process, it was observed that the components experienced excessive skewing, necessitating an update to the mesh system. Remeshing criteria were established, with a 0.2 mm change in strain and a 1 mm element size selected as the criteria for remeshing [12]. In Figure 2, the ECAPed material was modeled using both strain hardenable rigid-plastic modes and isotropic linear elastic modes.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…6 and Table 2). It must be mentioned that the precipitation sequence in the 7xxx al-loy is complicated and may contain simultaneously different metastable and stable phases such as θ, (η and η), (T and T) phases, or (S and S) phases depending on the Cu content and the Zn/Mg ratio [24].…”
Section: Microstructural Evolutionmentioning
confidence: 99%
“…In recent years, the micro-alloying of elements has gradually come into focus [1] .The addition of other elements to Al-Mg alloy to improve the properties of the alloy has been studied by domestic and foreign scholars, mainly focusing on trace elements such as Sc, Zr, etc [2][3][4][5] .However, the high price of Sc significantly increases production costs and is not conducive to price competition. The rare earth element Ce also achieves good performance improvements at a price advantage and is worth exploring for research purposes [6] .…”
Section: Introductionmentioning
confidence: 99%